Life cycle cost analysis and payback period of lighting retrofit at the University of Malaya - Mahlia, Teuku Meurah Indra; Razak, Hashim Abdul; Nursahida, M.A. (Elsevier, 2011)
This study presents the potential energy saving, life cycle cost analysis and payback period of the lighting system in campus buildings of the University of Malaya, Malaysia. The survey results indicate that almost 90 of the lighting system at the University Malaya campus consists of fluorescent lamp. Cost benefit analysis of retrofitting with more efficient lighting system in terms of potential energy saving, life cycle cost analysis and payback period have been conducted. Comparison of existing and retrofitting of lighting system based on the energy consumption is presented. From the analysis, it can be concluded that by using energy efficient lighting system will save a significant amounts of energy and cost, and also indirectly reducing emission.